Transcriptome analysis reveals differentially expressed genes and pathways for oviduct development and defense in prelaying and laying hens. (3rd July 2019) - Yin, Lingqian; Yu, Lintian; Zhang, Long; Ran, Jinshan; Li, Jingjing; Yang, Chaowu; Jiang, Xiaosong; Du, Huarui; Hu, Xiaofang; Liu, Yiping
Abstract: Problem: The oviduct plays an indispensable role in the formation of eggs, especially the magnum and uterus. The identification of oviduct development in different stages will help to target candidate genes and pathways in regulation of albumen and eggshell formation, as well as defense mechanism in oviduct and egg. Methods: To identify the function differences and the molecular defense mechanism of the oviduct and egg, we performed transcriptome sequencing analysis of the magnum and uterus in 120‐d‐old and 300‐d‐old Lohmann layers, three birds in each group. Results: With fold changes (log2 ratio) ≥ 2 and false discovery rate (FDR) < 0.01, RNA‐Seq revealed 1, 040 genes expressed differentially in the magnum and 595 genes in the uterus. By combining GO enrichment and KEGG pathway analysis, it served to show that gene activities of the magnum and uterus in prelaying chickens were more likely to concentrate on growth and development, and after egg‐laying, they were mainly inclined to enhance the substances transmembrane transport and secretion activities. We further characterized 1579 new genes, while only 803 of them were functionally annotated. A complex mixture of proteins related to defense was measured in this study. A subset of avian β‐defensins (AvBDs) and ovodefensins (OvoDs), that is, AvBD12, AvBD11, AvBD10, OvoDA1, OvoDB1, OvoDA2, OvoDA3, and OvoDBβ, was detected to express in the magnum of laying hens at high levels. Conclusion: Collectively, the identification and functional analysis of these differentially expressed genes (DEGs), as well as specific expression of avian defensins, may contribute to understand the development and defense mechanisms of oviduct and eggs. Abstract : The magnum and uterus of 120‐d‐old and 300‐d‐old Lohmann layers were used to perform RNA‐Seq, and the target candidate genes and pathways involved in albumen and eggshell formation, as well as defense mechanism were analyzed.